2005
DOI: 10.1021/la050256o
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Gelatin to a Polystyrene/Water Interface as a Function of Concentration, pH, and Ionic Strength

Abstract: The technique of neutron reflection has been used to investigate the adsorption of alpha-enriched gelatin from aqueous solution onto spun polystyrene substrates. Neutron reflection can provide information about the distribution of material perpendicular to an interface as well as total adsorbed amounts. The adsorbed layers were found to have maximum density at the surface, decaying with distance into solution. The adsorbed amount, layer thickness, and density were all seen to increase with solution concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…By further increase in pH, from 5 to 11, adsorption decreases. These observations are consistent with the finding of other studies [10,22,23]. It is well known that gelatin molecules achieve different charge densities and conformations at different pHs.…”
Section: Effect Of Phsupporting
confidence: 93%
“…By further increase in pH, from 5 to 11, adsorption decreases. These observations are consistent with the finding of other studies [10,22,23]. It is well known that gelatin molecules achieve different charge densities and conformations at different pHs.…”
Section: Effect Of Phsupporting
confidence: 93%
“…Depending on the pH of the medium, gelatin can exhibit properties of either a polyanion or a polycation, the net charge of the macromolecule being negative or positive, respectively. Therefore, its adsorption behavior is particularly interesting because the structure of the adsorbed layer varies with the pH, temperature, ionic strength, and concentration of the solution 7–9. A large amount of literature is available on the adsorption of gelatin 7–12.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, its adsorption behavior is particularly interesting because the structure of the adsorbed layer varies with the pH, temperature, ionic strength, and concentration of the solution 7–9. A large amount of literature is available on the adsorption of gelatin 7–12. In one of the early studies, Curme and Natale10 investigated the influence of the ionizing groups on the adsorption of gelatin onto silver bromide sol and concluded that the gelatin adsorption reaches maximum around its isoelectric point (IEP).…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] The adsorption of gelatin is particularly interesting because the structure of the adsorbed layer varies with pH, temperature, ionic strength and solution concentration. 20 In our previous study, we took advantage of the ease and flexibility of the electrostatic self-assembly method and the amphoteric natural of the gelatin, and adsorbed a single layer of gelatin as a polycation and polyanion to PLLA surface at pH 3.4 and 7.4, respectively, and found that the incorporation of a gelatin layer to the PLLA substrates significantly improved their cytocompatibility, with the gelatin treatment at pH 5 3.4 being most effective. 21 In this study, we attempted to assemble multiple layers of gelatin on charged PLLA substrates without using another polyelectrolyte as an interlayer by repetition of the adsorption and subsequent drying process, 22 which affords structurally regulated ultrathin gelatin films with controllable thicknesses.…”
Section: Introductionmentioning
confidence: 99%